Update on Metabolic Bariatric Surgery for Morbidly Obese Adolescents - Holger Till; Oliver Mann; Georg Singer; Susann Weihrauch-Blüher (MDPI AG, 2021)
Despite worldwide public attention and intense medical efforts, the prevalence of severe morbid obesity in children and adolescents is still rising. Similar to adults, excess adipose tissue triggers multiple immunological and metabolic pathways leading to serious co-morbidities such as impaired glucose tolerance or even type 2 diabetes (T2D), dyslipidemia, arterial hypertension, non-alcoholic fatty liver disease, and hyperuricemia. The management of severe childhood obesity requires a life-long multidisciplinary approach with a combination of lifestyle changes, nutrition, and medications. Standardized life-style intervention programs remain the first-line treatment for morbid obese children and adolescents, but unfortunately reveal limited long-term success. In such cases, metabolic bariatric surgery (MBS) has evolved from being a controversial issue to being included in distinct recommendations. According to the American Society for Metabolic and Bariatric Surgery (ASMBS) Pediatric Committee, indications for bariatric surgery in adolescence must follow very strict criteria. Adolescents with class II obesity (BMI > 120% of the 95th percentile) and a diagnosed co-morbidity or with class III obesity (BMI ≥ 140% of the 95th percentile) should be considered for MBS. These interventions represent high-risk operations, and adolescents should be treated in specialized, multidisciplinary high-volume obesity centers with long-term follow-up programs. The Roux-en-Y gastric bypass (RYGB) remains the gold standard of all malabsorptive procedures. Laparoscopic sleeve gastrectomy (LSG), which the authors pioneered as a stand-alone procedure in morbidly obese adolescents in 2008, has become the most commonly performed operation in morbidly obese adolescents at present. Recent literature proves that MBS is safe and effective in morbidly obese adolescents. Mid-term data have revealed significant improvement or even resolution of major co-morbidities. Thus, MBS for the treatment of morbidly obese adolescents has evolved from being a controversial issue to being included in distinct recommendations by several medical societies as a therapeutic strategy to reduce severe co-morbidities potentially causing end-organ damage in adulthood.